Effect of conjugated estrogens/bazedoxifene on postmenopausal bone loss: pooled analysis of two randomized trials. Issue 10 (October 2016) - Gallagher, J. Christopher; Palacios, Santiago; Ryan, Kelly A.; Yu, Ching-Ray; Pan, Kaijie; Kendler, David L.; Mirkin, Sebastian; Komm, Barry S.
Abstract: Objective: Conjugated estrogens/bazedoxifene reduces vasomotor symptoms and prevents postmenopausal bone loss without stimulating the breast and endometrium. We analyzed changes in bone mineral density (BMD) and bone markers using pooled data from two phase-3 trials. Methods: Selective Estrogens, Menopause, and Response to Therapy (SMART)-1 and SMART-5 were randomized, double-blind, placebo- and active-controlled studies conducted in postmenopausal nonhysterectomized women. BMD and turnover marker data were pooled for women given conjugated estrogens (0.45 or 0.625 mg) plus bazedoxifene 20 mg or placebo over 12 months. Sensitivity analyses were conducted using baseline Fracture Risk Assessment Tool score, age, years since menopause, body mass index, race, and geographic region. Results: There were 1, 172 women, mean age 54.9 years, mean 6.21 years since menopause, mean lumbar spine, and total hip T scores −1.05 and −0.58; 58.8% had a Fracture Risk Assessment Tool score less than 5% indicating low fracture risk. At 12 months, adjusted differences (vs placebo) in BMD change in the groups taking conjugated estrogens 0.45 or 0.625 mg plus bazedoxifene 20 mg were 2.3% and 2.4% for lumbar spine, 1.4% and 1.5% for total hip, and 1.1% and 1.5% for femoral neck (all P < 0.001 vs placebo). These increases were unrelated to baseline Fracture Risk Assessment Tool score, age, years since menopause, body mass index, or geographic region. Both doses reduced bone turnover markers ( P < 0.001). Conclusions: Conjugated estrogens/bazedoxifene significantly improved BMD and turnover in a large population of younger postmenopausal women at low fracture risk and is a promising therapy for preventing postmenopausal bone loss.